Assessment of Topical Steroid-damaged/ Dependent Face Severity Score and its Impact on Quality of Life: A Cross-sectional Study - Vishakha Goel; Deepika Agarwal; Suganita; Sonal Sachan; Vandana Yadav; Ankur Talwar (Journal of Clinical and Diagnostic Research)
Introduction: Topical Corticosteroids (TCS) are injudiciously used by the general population for face dermatosis resulting in constitution of symptoms called topical steroid damaged/dependent face which directly/indirectly affect the mental well-being and self-esteem of patients. Aim: To study dermoscopic features of Topical Steroid-damaged/Dependent Face (TSDF) and measure its severity using dermoscopy-assisted topical steroid damaged/Dependent Face Severity (DATS) score and its impact on Quality of Life (QoL) using Dermatology Life Quality Index (DLQI). Materials and Methods: The study was a hospital-based cross-sectional study conducted at Dermatology Outpatient Department, Hind Institute of Medical Sciences, Barabanki, Uttar Pradesh, India, from June 2023 to May 2024 that enrolled 188 patients aged 16-45 years having clinical features of TSDF. Demographic data like age, gender, residence, occupation, education and details on TCS namely type, indication, frequency, duration and prescriber other than dermatologist were collected, clinical features and dermoscopic findings were evaluated using DATS score and QoL using DLQI score. Fischer’s-exact test was used to compare quantitative variables. Analysis of Variance (ANOVA) was used for more than two variables. The p-value <0.05 was considered statistically significant. Results: The mean age of the study population was 27.1±7.6 years. The mean DATS score was 22.7±8.1. The mean DLQI score was 11.3±3.3. Positive association and correlation were observed between DATS and DLQI scores (p<0.001 and r=0.612). Conclusion: The TSDF affected the QoL in the study participants and DLQI scores helped to segregate patients according to severity so that prompt referral to the specialised clinics could be done.